Analysis of Abnormality based on Size in Red Blood Cells in Peripheral Blood Smear Images - Sheeba, F; Robinson, T; Mammen, JJ; Philips, JMS; Sathyaraj, T; Prabhu, SV (International Journal of Computer Sciences and Engineering, 2025)
The diagnostic formulations in patients rest on a tripod consisting of clinical history, physical examination and laboratory investigations. In most of the cases diagnoses are mainly done based on laboratory medicine. Current manual techniques lack precision and reproducibility and hence automated methods where an image of the smear is captured and analyzed offers more precision and accuracy. Accurate analysis of the cells including the red cells in the blood smear images is vital for the diagnosis of various diseases and pathological conditions in patients. This calls for accurate detection and segmentation of the Red Blood Cells (RBCs) prior to analysis. Normal RBCs are biconcave in shape with a central pale area and any deviation in most of the RBCs in their size and ratio of the total surface area of the cell to the central pale area from the normal represents an abnormality. If the size and volume of an RBC is less than a normal cell it is indicative of a pathological process called as microcytosis and on the other hand macrocytosis is the condition where the cell is enlarged. This paper proposes an automated method of analyzing the RBCs in blood smear images for morphological abnormalities, which is an extension of an earlier work focusing on segmentation of all the cells in the blood smear images using Watershed Transform.